Uji Fisik Dan Stabilitas Formulasi Sediaan Masker Gel Dari Ekstrak Daun Beluntas (Pluchea Indica L.) dengan Variasi Karbopol sebagai Gelling Agent - Rahmawati, Zendy Lia Ayu; Budiawan, Antonius; Puradewa, Levi (STIKes Ibnu Sina Ajibarang, 2025)
Beluntas (Pluchea indica L.) contains of flavonoids, which are beneficial for treating acne. Previous research has been conducted on peel-off gel masks made from ethanol extract of beluntas leaves. The aim of this study is to determine the variation in carbopol concentrations in the formulation of gel masks containing beluntas leaf extract, as well as to evaluate their physical stability. This research using three formulations with different carbopol concentrations: Formula I with 1% carbopol, Formula II with 1.5% carbopol, and Formula III with 2% carbopol. The physical evaluation of the beluntas leaf extract gel mask preparations included organoleptic, homogeneity, viscosity, pH, spreadability, and adhesiveness testing. All formulations underwent a stability test known as the cycling test (cycles 1 to 6). The results of the stability tests showed that Formulas II and III met the requirements for physical quality, whereas Formula I did not meet the viscosity and spreadability value ranges. The gel mask with the best results was Formula II with 1.5% carbopol concentration. However, based on the cycling stability test, there was an increase in viscosity and adhesiveness. Based on the cycling test results for organoleptic properties, homogeneity, and spreadability, Formula II did not show significant changes.